2019
DOI: 10.1371/journal.pone.0213127
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the SMAD2/3 signalling pathway in the down regulation of megalin/LRP2 by transforming growth factor beta (TGF-ß1)

Abstract: Megalin/LRP2 is a receptor that plays important roles in the physiology of several organs, such as kidney, lung, intestine, and gallbladder and also in the physiology of the nervous system. Megalin expression is reduced in diseases associated with fibrosis, including diabetic nephropathy, hepatic fibrosis and cholelithiasis, as well as in some breast and prostate cancers. One of the hallmarks of these conditions is the presence of the cytokine transforming growth factor beta (TGF-ß). Although TGF-ß has been im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 116 publications
(162 reference statements)
0
17
0
1
Order By: Relevance
“…Additionally, one population-based study linked polymorphisms within the megalin gene with the progression of prostate cancer [ 62 ]. Interestingly, megalin mRNA and protein levels were found to decrease in kidney and gallbladder epithelial cell lines upon in vitro activation of transforming growth factor-beta (TGF-ß1)—SMAD2/3 signaling pathway [ 63 ], which is well known for its tumor-suppressive effect [ 64 ]. As megalin is a multiligand receptor, to clarify its role in tumor growth, attention should be paid to its interaction with possible ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, one population-based study linked polymorphisms within the megalin gene with the progression of prostate cancer [ 62 ]. Interestingly, megalin mRNA and protein levels were found to decrease in kidney and gallbladder epithelial cell lines upon in vitro activation of transforming growth factor-beta (TGF-ß1)—SMAD2/3 signaling pathway [ 63 ], which is well known for its tumor-suppressive effect [ 64 ]. As megalin is a multiligand receptor, to clarify its role in tumor growth, attention should be paid to its interaction with possible ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Diwakar et al (2007) using OK cells showed that albumin induces TGF-β secretion. Recently, Cabezas et al (2019) using LLC-PK1 cells showed that TGF-β decreases megalin expression. Accordingly, we observed an increase in the TGFβ level in the BSA groups.…”
Section: Discussionmentioning
confidence: 99%
“…LRP2 encodes the LDL receptor related protein, also termed megalin. LRP2/megalin plays a role in cellular signaling for growth pathways by facilitating endocytosis of various ligands including hormones, lipoproteins, vitamins, and sterols [25] . The TTN protein is a large protein found in muscle and is responsible for passive elasticity.…”
Section: Discussionmentioning
confidence: 99%